Understanding Osteoporosis and its Ayurvedic Management - A Review (International Journal of Ayurveda and Pharma Research, 2022)
Osteoporosis is a generalized skeletal disorder of low bone mass and deterioration in its architecture causing susceptibility to fracture. Multiple etiological factors like physical, hormonal, nutritional and life style contribute to the development of disease. It usually generates along with senile and postmenopausal changes in the body. Morbidity associated with Osteoporotic fracture is on the rise. Currently the disease is increasing in much earlier groups, owing to present lifestyle. So preventive strategies should be adopted much earlier as maintaining a healthy life style itself can protect against fractures in later life. As disease prevention and treatment have improved over last two decades, public awareness of Osteoporosis remains minimal particularly in rural areas. Conventional medications are often effective for symptomatic relief only. However this provides much scope to Ayurveda, which aims at treatment as well as disease prevention. It can be considered as a disease characterized by localization of vitiated Vata in Asthi Dhatu i.e.; ‘Asthigata Vata’ resulting in Asthi Kshaya. Vata Kopa and Asthikshaya can result in osteoporosis. Condition can be managed in Ayurveda adopting Asthigata Vata Chikitsa, Asthikshaya chikitsa, Bhagna chikitsa and usage of drugs with Brimhana, Rasayana and Vata Hara property.